RISE OF ECLECTICISM IN THE 21ST CENTURY MALAYSIAN MOSQUE ARCHITECTURE - Zekrgoo, Amir Hossein (PLANNING MALAYSIA, 2017)
A stylistic survey of Malaysian mosque architecture shows four distinct trends: 1) Traditional style, which covers most of the mosques that were built before the country’s independence in 1957; 2) Colonial style that was influenced by Indian Mughal architecture, was followed partly after independence, and continued for a while after that; 3) Modern trend began with the National Mosque completed in 1965, and scattered mosques that were built after the National Mosque until the end of the 20th century; and 4) Mosques that were erected in the 21st century, which can be generally explained by the term ‘eclectic’ design. Eclecticism gained rapid momentum in the field of Malaysian mosque architecture since the dawn of the current century. Significant eclectic mosques that have transformed the scene and skylines of major Malaysian cities have often been heavily financed by the government – an indication of conscious choice of direction. This paper aims at providing a categorisation of the process of evolution of contemporary mosque architecture in Malaysia, not based on independent stylistic tendencies, but under three major historical/thematic phases: 1) Independence and Departure from Tradition; 2) Middle Eastern Inspirations; and 3) Rise of eclecticism, with an emphasis on the last phase, i.e. rise of eclecticism in the 21st century. Masjid Wilayah, completed in August 2000, was chosen as a case study because it is the first major eclectic mosque born in the 21st century, incorporating some six established styles, and also the most comprehensive example.